Fog learning for cultivating critical thinking in information seeking process. (16th October 2018) - Haghparast, Mahboobeh; Abdullah, Noorhidawati; Nasaruddin, Fariza Hanum
Summary: Fog computing has been emerged as a promising paradigm with the different applications from industry to academic area. In this paper, we proposed a new concept, namely fog learning with the aim of addressing the critical thinking as a demanding issue in academic area. Due to the distributed architecture of our fog learning model, it can be used anywhere, anytime, and with the minimum latency in comparison with the existing mobile and cloud learning models to foster the critical thinking. To test the effectiveness of the proposed method, we applied the Software Usability Measurement Inventory (SUMI) as well as the acceptance test. We firstly showed that more than 74% of participants suffered from lack of critical thinking. Moreover, the participants indicated that they use several critical thinking skills during information seeking process, which shows there are relationships between critical thinking skills and the information seeking processes. According to the relationships between critical thinking skills and the information seeking processes, we designed a prototype for cultivating of critical thinking on the basis of fog learning. The results of the prototype evaluation emphasized on its positive role to foster critical thinking.